Financial stress, regime switching and macrodynamics: Theory and empirics for the US, the EU and non-EU countries - Willi Semmler; Pu Chen (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
Over-borrowing and financial stress has recently become an important issue in macroeconomic and policy discussions in the US as well as in the EU. In this paper the authors study two regimes of financial stress. In a regime of high financial stress, stress shocks can have large and persistent impacts on the real side of the economy whereas in regimes of low stress, shocks can easily dissipate having no lasting effects. In order to study the macroeconomic dynamics, with alternative paths resulting from financial stress shocks, the authors introduce a macromodel with a finance-macro link which uses a multi-period decision framework of economic agents. The agents can, in a finite horizon context, borrow and accumulate assets where however the above two scenarios may occur. The model is solved through nonlinear model predictive control (NMPC). Empirically the authors use a multi-regime VAR (MRVAR) to study the impact of financial stress shocks on the macroeconomy in a large number of countries.
Keywords: E3; G21; 330; Financial Stress; Macro dynamics; MRVAR